Implementation of Google Sites in Developing Environmental Education Based on Socio-Scientific Issues and Islamic Integration to Enhance Environmental Literacy - Mufatihatut Taubah; Dwiyani Anjar Martitik; Muhammad Naufal Muzakki; Didi Nur Jamaludin (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2025)
Environmental education is increasingly recognized as an essential thing from preschool to higher education. Environmental sustainability is vital for the survival of humans and all living organisms. The use of digital technology tools such as Google Sites can serve as an effective learning medium in environmental education. This study adopts the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. This study aimed to develop a Google Sites-based medium for environmental education based on Socio-Scientific Issues and Islamic Integration. The study was conducted with first-semester students in the biology education program. The validity assessment of the Google Sites media for environmental education showed a highly valid category in both material and design aspects. The implementation of Google Sites media produced significant results in enhancing students’ environmental literacy. Students rated the Google Sites media very good as an environmental education based on Socio-Scientific Issues and Islamic Integration. In particular, the 'Environmental Creation' feature received positive feedback. These findings suggest that environmental education using Google Sites can be further developed to enhance students’ creativity and assessment literacy, for learning media at school and higher education levels and can be combined with the TPACK framework, project and problem based learning.